2017
DOI: 10.1074/jbc.m117.780551
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated extracellular loop mutations in the adhesion G protein-coupled receptor G1 (ADGRG1; GPR56) differentially regulate downstream signaling

Abstract: Mutations to the adhesion G protein-coupled receptor ADGRG1 (G1; also known as GPR56) underlie the neurological disorder bilateral frontoparietal polymicrogyria. Disease-associated mutations in G1 studied to date are believed to induce complete loss of receptor function through disruption of either receptor trafficking or signaling activity. Given that N-terminal truncation of G1 and other adhesion G protein-coupled receptors has been shown to significantly increase the receptors' constitutive signaling, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…Mutant GPCRs are often overexpressed and constitutively active in various cancers ( Dorsam and Gutkind, 2007 , Kan et al., 2010 , O'Hayre et al., 2013 ). Disease-associated mutations were previously reported to change other adhesion GPCR signaling ( Kishore and Hall, 2017 , Purcell et al., 2017 ). We tested cancer-associated mutations of Lphns reported in different types of carcinomas ( Kan et al., 2010 , O'Hayre et al., 2013 ) and found that the cancer-associated mutations affected basal activity and/or peptide response ( Figure 4 E).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant GPCRs are often overexpressed and constitutively active in various cancers ( Dorsam and Gutkind, 2007 , Kan et al., 2010 , O'Hayre et al., 2013 ). Disease-associated mutations were previously reported to change other adhesion GPCR signaling ( Kishore and Hall, 2017 , Purcell et al., 2017 ). We tested cancer-associated mutations of Lphns reported in different types of carcinomas ( Kan et al., 2010 , O'Hayre et al., 2013 ) and found that the cancer-associated mutations affected basal activity and/or peptide response ( Figure 4 E).…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs have recently become a hot topic in tumor research ( 19 21 ). They are reported to be vital regulators of various cellular functions such as cell adhesion, migration, polarity, and guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Although their protein architectures remain largely unknown, functional studies have shown that aGPCR ECRs can regulate receptor function and that antibody-like synthetic proteins that target the ECRs can modulate downstream signaling 9,[22][23][24][25] . A current model for aGPCR regulation suggests that transient interactions between the ECR and 7TM directly regulate receptor signaling 9,[22][23][24][25] . There are also numerous reports that aGPCRs use their ECRs to mediate functions in a 7TM-independent manner [26][27][28][29][30] .…”
mentioning
confidence: 99%